Chemiluminescence noncompetitive immunoassay based on microchip electrophoresis for the determination of β-subunit of human chorionic gonadotropin - Li, Shuting; Yang, Tingzheng; Zhao, Jingjin; Huang, Yong; Zhao, Shulin (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2017)
•A simple MCE-CL immunoassay was developed for the detection of tumor marker β-HCG.•Proposed assay method is suitable for quantification of β-HCG in human serum.•Lower sample and reagent consumption in MCE provide good separation and quick assay. In this work, a microchip-electrophoresis chemiluminescence (MCE-CL)-based immunoassay method was established for the determination of β-subunit of human chorionic gonadotropin (β-HCG). This approach uses MCE-CL assay as a platform. First, the β-HCG antigen (Ag) binds to excess horseradish peroxidase (HRP)-labeled anti-β-HCG antibodies (Ab*) to form an immune complex (Ag-Ab*). Subsequently, the obtained Ag-Ab* complex and unreacted Ab* were separated by MCE, and detected by CL. The CL intensity (peak high) of Ag-Ab* was used to estimate β-HCG concentration. The calibration curve between the peak high and β-HCG concentration showed a good linearity in the range of 0.6–60mIU/mL. Based on a signal/noise ratio (S/N) of 3, the detection limit for β-HCG was estimated to be 0.36mIU/mL. The present method was successfully applied for the detection of β-HCG in human serum, and the serum content of β-HCG from three healthy subjects was found be in the range of 9.5–15.7mIU/mL, while that from three ovarian cancer patients was found be in the range of 160.9–210.4mIU/mL. These results suggest that cancer patients have higher contents of β-HCG than healthy individuals do, indicating that this method can be applied for assisting diagnosis of ovarian cancer in clinical application.